Hubungan Antara Indeks Massa Tubuh dengan Daya Tahan Kardiovaskuler - Abu Musa Al Blitari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Cardiovascular endurance is a crucial component of physical fitness, reflecting the ability of the heart, lungs, and circulatory system to effectively supply oxygen during physical activity. This ability plays a crucial role in supporting daily activities and maintaining overall health. One factor thought to influence cardiovascular endurance is the Body Mass Index (BMI), which is used as an indicator of a person's nutritional status based on the ratio of body weight to height. Abnormal BMI values, whether too low or too high, can impact the body's physiological functions, particularly the cardiovascular system. This study aims to analyze the relationship between BMI and cardiovascular endurance through a literature review method. Data were collected from various national and international scientific journals relevant to the research topic over a specific time period, then analyzed descriptively and comparatively to obtain a comprehensive picture. The results of the study indicate that individuals with a normal BMI tend to have better cardiovascular endurance compared to individuals with a low or high BMI (overweight or obese). A high BMI is associated with decreased cardiovascular efficiency due to increased body fat, while a BMI that is too low can also impact physical capacity due to limited energy reserves. However, the relationship between BMI and cardiovascular endurance is not simple. Other factors such as physical activity level, age, gender, and lifestyle also influence the condition. Therefore, it can be concluded that there is a relationship between BMI and cardiovascular endurance, but this relationship is complex and influenced by various other factors that interact dynamically.